The value of delegated quality control - Saak, Alexander E. (Wiley, 2017)
This paper studies the case in which a firm delegates quality control to an independent monitor. In a repeated game, consumers’ trust provides incentives to acquire information about whether the good is defective, and withhold defective goods from sale. If third‐party reports are observable to consumers, delegation lessens the first and dispenses with the second moral hazard concern but also creates agency costs. Internal quality control is optimal only if trades are sufficiently frequent and consumer information is sufficiently precise. This result holds in the presence of the possibility of collusion, fully non‐verifiable presale information, and economies of scale in external quality control.